(untitled) (Economic and Political Thought, 2018)
The aim of the article is to identify factors that significantly affect the level of R&D and to determine the strength of this impact. The research involved 950 Polish logistics companies. Data from the Local CSO Data Bank from 2007–2015 were used for the study. As explanatory variables, three groups of potential R&D determinants of the studied entities were distinguished: intensity of competition, financial performance of the enterprise and macroeconomic conditions. The analysis was based on descriptive statistics, Pearson’s correlation analysis and Spearman’s rank correlation coefficient and the use of panel models, estimated on the basis of a cross-sectional sample. The statistical survey was carried out both on aggregate national values and using data at the voivodship level. The study showed that R&D activities of logisticsfirms are carried outprimarily by larger companies, which conduct a conservative financing policy based on low indebtedness and high liquidity.These firms operate in a low marginenvironment, which significantly limits development opportunities. The study did not confirm the impact of competition on R&D activity, which may result from the growth of the sector itself. However, the availability of road infrastructure and urbanized areas is a factor that indisputably affects R&D.